(untitled) (MMIT Proceedings, 2026)
This study develops an integrated model for assessing corporate financial stability based on liquidity, solvency, profitability, and turnover indicators. Using data for 2020–2025, the Integral Stability Index (IBS) was calculated and its sensitivity to macroeconomic factors was evaluated through regression analysis. The findings confirm that financial stability is significantly influenced by leverage and profitability levels.